Efisiensi Energi Bahan Bakar Sekam dan Kayu pada Proses Sterilisasi Media Tumbuh Jamur Tiram Putih - Abdul Djamil Husin; . Irzaman; Jajang Juansah; Touwil Umrih; Khafit Pratama Hendratno; Ella Rahmadani; Sumarjono Effendy (Institut Pertanian Bogor, 2012)
We have investigated the sterilization at media pleurotus otreatus using rice husk fuel and wood in various 6, 8 and 10 hours. We carried out efficiency energy for pleurotus otreatus medium sterilization at 8 hours using rice husk fuel is 14.28%, whereas efficiency energy for pleurotus otreatus medium sterilization using wood is 17.35%. The results show that cooking stove from rice husk are suitable for use as renewable energy technology applications to support E3i village (Energy, Economics and Environment).